2009
DOI: 10.2340/16501977-0403
|View full text |Cite
|
Sign up to set email alerts
|

Robot-mediated therapy for paretic upper limb of chronic patients following neurological injury

Abstract: The results confirm that robot-mediated therapy, through short-term, but intensive, repetitive and goal-directed trials, contributes to a decrease in the upper limb's motor disability in people with a chronic neurological injury by reducing motor impairment and shoulder pain. The treatment was well accepted and tolerated by patients. No adverse events occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Our results confirm that the motor impairment in the upper limb of post-stroke patients improve after the rehabilitation based on a robot-aided therapy, both in chronic and subacute subjects, as demonstrated by several previous studies [22], [23], [24], [25], [26], [27], [28], [29], [30], even if clinical scales seem to detect a better recovery in subacute patients than that observed in chronic patients. The analysis of biomechanical parameters shows that also the velocity of the arm movement improves after the robotic training, in both groups (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirm that the motor impairment in the upper limb of post-stroke patients improve after the rehabilitation based on a robot-aided therapy, both in chronic and subacute subjects, as demonstrated by several previous studies [22], [23], [24], [25], [26], [27], [28], [29], [30], even if clinical scales seem to detect a better recovery in subacute patients than that observed in chronic patients. The analysis of biomechanical parameters shows that also the velocity of the arm movement improves after the robotic training, in both groups (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…A robot-assisted device can provide repetitive, task-specific activities that can be graded to challenge the user to promote motor learning without the direct one-on-one oversight of a therapist (Kwakkel et al, 2008;Masiero et al, 2009;Matsuo et al, 2013). An emerging body of evidence has shown promising results with improved motor recovery and improvement on QOL measures with the use of robotic devices after stroke (Bovolenta, Sale, Dall'Armi, Clerici, & Franceschini, 2011;Page, Hill, & White, 2013;Posteraro et al, 2009). Page et al (2013) found that after 24 sessions with an upperextremity (UE) robot-assisted therapy device, people with chronic stroke made favorable gains in the ADL and Instrumental Activities of Daily Living (IADL), Hand Function, and Stroke Recovery domains of the Stroke Impact Scale (SIS; Duncan et al, 1999), a QOL measure used after stroke (Page et al, 2013).…”
mentioning
confidence: 99%
“…The motor improvement in the upper limb impairment of post-stroke patients after the rehabilitation based on a robot-aided therapy has been demonstrated by several previous studies [8,10,15,16,19,20,22,24,30].…”
Section: Discussionmentioning
confidence: 90%